Tracking human contact allergens: from mass spectrometric identification of peptide-bound reactive small chemicals to chemical-specific naive human T-cell priming - Dietz, Lisa; Esser, Philipp Ralf; Schmucker, Sonja; Goette, Irina; Richter, Anne; Schnölzer, Martina; Martin, Stefan F.; Thierse, Hermann-Josef (Toxicological sciences, 2010)
Modification of proteins by reactive small chemicals is a key step in the activation of chemical-specific T cells in allergic contact dermatitis (ACD). However, an integrated approach to characterize both the precise nature of chemically modified proteins and the chemical-specific T cells is currently lacking. Here, we analyze the molecular conditions for adduct formation of the strong human contact sensitizer 2,4-dinitrochlorobenzene (DNCB) and its water-soluble form, 2,4-dinitrobenzenesulfonic acid (DNBS), with both an all amino acid-containing model peptide (± Cys) and the protein human serum albumin (HSA). Mass spectrometric detection and quantification revealed thiol-dependent peptide adduct formation at all pH values found in human skin layers. Highest modification rates were obtained with DNBS. Accordingly, DNBS- but not DNCB-modified human immature dendritic cells (iDC) induced in vitro primary human T-cell responses as did 2,4,6-trinitrobenzenesulfonic acid-modified iDC as measured by dinitrophenyl (DNP)- and trinitrophenyl (TNP)-specific T-cell proliferation and interferon gamma (IFN-γ) production in CD4+ and CD8+ T-cell subsets. Moreover, DNP-modified HSA protein effectively induced primary T-cell responses when processed by iDC. Thus, an integrated approach that combines efficient skin-related in chemico coupling analyses with an in vitro T-cell priming assay can be used to predict in vivo reactions of chemical contact allergens with extracellular and cellular proteins. This strategy supports the development of chemical-specific in vitro assays that are urgently required in predictive hazard identification and risk assessment of allergenic and nonallergenic chemicals.
Gesehen am 02.02.2023